Pengaruh pH dan Konsentrasi Larutan terhadap Penyerapan Ion Pb²⁺ pada Tanah Napa Pesisir Selatan dengan Metode Kolom - Shintia Ayu Alhadina; Mawardi Mawardi (MASALIQ, 2025)
The rapid development of industry, driven by advances in technology and science, has brought economic benefits but also generated waste with the potential to pollute the environment, particularly aquatic systems. One contaminant of concern is the Pb²⁺ metal ion, known for its toxicity. This study aims to utilize tanah napa from Balai Selasa, Ranah Pesisir, Pesisir Selatan Regency as an adsorbent for Pb²⁺ ions in wastewater. Tanah napa was selected due to its high silica and alumina content, porous structure, and the presence of active groups such as silanol (Si–OH), silica (Si–O), and siloxane (Si–O–Si). Characterization of the material was conducted using Fourier Transform Infrared Spectroscopy (FTIR). Adsorption tests were performed continuously using the column method with variations in concentration and pH. The reduction of Pb²⁺ levels was analyzed using Atomic Absorption Spectrometry (AAS). Results indicated that optimal conditions occurred at a concentration of 250 ppm and pH 4. The adsorption process followed the Langmuir isotherm model with a correlation coefficient of R² = 0.9862 and a maximum adsorption capacity of 3.3467 mg/g. The study concludes that tanah napa has significant potential as a cost-effective and efficient adsorbent for Pb²⁺ ions, offering an alternative solution for industrial wastewater treatment at both laboratory and field application scales.